2019
DOI: 10.1093/cid/ciz728
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors for Invasive Pneumococcal Disease and Community-acquired Pneumonia in Human Immunodeficiency Virus–Infected Individuals in a High-income Setting

Abstract: Background Although people living with human immunodeficiency virus (PLWH) are at increased risk of invasive pneumococcal disease (IPD) and community-acquired pneumonia (CAP), it is unclear whether this remains the case in the setting of early initiation of combination antiretroviral therapy (cART), at high CD4 cell counts. This is important, as pneumococcal vaccination coverage in PLWH is low in Europe and the United States, despite longstanding international recommendations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…As these cells are known to be highly permissive to HIV infection and serve as reservoirs during chronic infection, they could potentially explain these disrupted B/T cell interactions (64)(65)(66). Clinically, compromised B/T cells interactions may contribute to impaired immune responses to vaccination as well as increased risks for infections, such as invasive pneumococcal disease (5,67). Finally, improvement of B/T cell communication is crucial for the development of broadly neutralizing antibodies and thus functional cure in PLHIV (68).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As these cells are known to be highly permissive to HIV infection and serve as reservoirs during chronic infection, they could potentially explain these disrupted B/T cell interactions (64)(65)(66). Clinically, compromised B/T cells interactions may contribute to impaired immune responses to vaccination as well as increased risks for infections, such as invasive pneumococcal disease (5,67). Finally, improvement of B/T cell communication is crucial for the development of broadly neutralizing antibodies and thus functional cure in PLHIV (68).…”
Section: Discussionmentioning
confidence: 99%
“…Combination antiretroviral therapy (cART) has drastically curtailed morbidity and mortality in people living with HIV (PLHIV) (1). Still, PLHIV remain at an increased risk for pneumococcal infections, Mycobacterium tuberculosis (M. tuberculosis) reactivation and impaired vaccine responses (2)(3)(4)(5)(6). Moreover, HIV infection predisposes to non-infectious comorbidities, such as cardiovascular disease and non-AIDSrelated cancer, which share an underlying pathophysiological pathway characterized by a persisting and inappropriate activation of innate and adaptive immune cells (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…The durability of the immune response following pneumococcal vaccination is an important issue, even more so as life expectancy of PLWH under cART has nowadays approximated that of HIV-negative counterparts. In addition, the risk of pneumococcal infections increases at more advanced age [1] . With respect to the durability of the immune response, PCV is often thought to be superior, because PPSV23 does not induce immunologic memory [5 , 65] .…”
Section: Discussionmentioning
confidence: 99%
“…People living with HIV (PLWH) are at increased risk of pneumococcal disease, even in the era of advanced combination antiretroviral therapy (cART). A recent study showed an incidence rate of pneumococcal disease in PLWH of 190 per 100,000 patient-years of follow-up, compared to 38 per 100,000 in the general population [1] . Pneumococcal disease in PLWH often requires hospitalisation, and mortality rates range up to 25% [2].…”
Section: Introductionmentioning
confidence: 99%
“…People living with human immunodeficiency virus (HIV) are at an increased risk of invasive pneumococcal disease (IPD), 1–3 being at least seven times more likely to develop IPD, independent of other known risk factors 4 or CD4 count, 2 resulting in significant mortality and morbidity. In addition, IPD may be the first presentation to healthcare for people living with HIV, 5,6 providing an opportunity for earlier diagnosis of HIV.…”
mentioning
confidence: 99%